The Effect of Training on Employee Performance at PT. Digiprint Innovation Indonesia in Tangerang - Yoke Sukma Indhiradita (Peneliti.net, 2023)
This study aims to determine the effect of training on employee performance at PT Digiprint Innovation Indonesia in Tangerang. The method used is explanatory research with a sample of 75 respondents. The analysis technique uses statistical analysis with regression testing, correlation, determination and hypothesis testing. The results of this research variable Training obtained an average score of 3.799 with good criteria. Employee performance variable obtained an average score of 3.889 with good criteria. Training has a significant effect on employee performance with the regression equation Y = 14.193 + 0.650X, and a correlation value of 0.763 or strong with a determination of 58.3%. The hypothesis test obtained a significance of 0.000 <0.05.